Deforming grid generation for numerical simulations of fluid dynamics in sliding vane rotary machines. (October 2017) - Bianchi, Giuseppe; Rane, Sham; Kovacevic, Ahmed; Cipollone, Roberto
Highlights: Development of a novel grid generation methodology for sliding vane rotary machines based on user defined nodal displacement. Mesh boundaries are defined as parametric curves generated using trigonometrical modelling of the axial cross section of the machine. Distribution of computational nodes is performed using algebraic algorithms with transfinite interpolation, post orthogonalisation and smoothing. Grid quality is enhanced through algebraic control functions for distribution of the nodes on the rotor and casing boundaries. Generated grids have been tested on single phase CFD simulations using FLUENT and CFX solvers. Abstract: The limiting factor for the employment of advanced 3D CFD tools in the analysis and design of rotary vane machines is the unavailability of methods for generation of a computational grid suitable for fast and reliable numerical analysis. The paper addresses this issue through an analytical grid generation based on the user defined nodal displacement which discretizes the moving and deforming fluid domain of the sliding vane machine and ensures conservation of intrinsic quantities by maintaining the cell connectivity and structure. Mesh boundaries are defined as parametric curves generated using trigonometrical modelling of the axial cross section of the machine while the distribution of computational nodes is performed using algebraic algorithms with transfinite interpolation, post orthogonalisation and smoothing. Algebraic control functions are introduced for distribution of nodes on the rotor and casing boundaries in order to achieve good grid quality in terms of cell size and expansion. For testing of generated grids, single phase simulations of an industrial air rotary vane compressor are solved by use of commercial CFD solvers FLUENT and CFX. This paper presents implementation of the mesh motion algorithm, stability and robustness experienced with the solvers when working with highly deforming grids and the obtained flow results.